IMPLEMENTATION OF ISO 9001 QUALITY MANAGEMENT SYSTEM IN UNS CENTER LIBRARY - Finna Aqhninna; Wiedy Murtini; Cicilia Dyah S. Indrawati (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2021)
The purpose of this study was studied to determine the implementation of the ISO 9001 Quality Management System in the UNS Central Library. The research method used is qualitative with a phenomenal approach. The phenomena that have occurred are the transformation of ISO 9001, program innovation carried out by the UNS Central Library, and Predicate A for the National University Libraries. The results of this study were reviewed by 10 ISO clauses with the PDCA pattern (Plann, Do, Check, and Act). So that getting a program that has been running includes Processing Library Materials, Cooperation Administration, Digital Library Services, Academic Internships, Maintenance of Infrastructure, Website Management, Book Returns, HR, Information Literacy, Scientific Library Clinics, Library Tours, News Coverage, Environmental Maintenance, to the processing of journals, magazines, and newspapers. All of these programs are the result of implementing ISO 9001 itself by compiling Quality Procedures and Work Instructions for all elements of the UNS Central Library.